(untitled) (American Journal of Islam and Society, 2012)
Sayyid Qutb’s reputation as one of the finest Muslim writers of all time is based on the quality of his writings in terms of their eloquence and ideas. For example, his F¥ ilOEl al-Qur’OEn is one of the best, captivating, and most widely read Qur’anic commentaries in the Middle East. But in the West his reputation as a writer has been effectively eclipsed mainly because of political considerations. Here, he is generally portrayed as the leading ideologue for the Muslim Brotherhood or al-Qaeda. Rather than perpetuate this negative impression, this editorial seeks to highlight the literary and artistic dimensions of his ilOEl.